Disease trajectories, place and mode of death in people with head and neck cancer: Findings from the 'Head and Neck 5000' population-based prospective clinical cohort study. (May 2020) - Mayland, Catriona R; Ingarfield, Kate; Rogers, Simon N; Dey, Paola; Thomas, Steven; Waylen, Andrea; Leary, Sam D; Pring, Miranda; Hurley, Katrina; Waterboer, Tim; Pawlita, Michael; Ness, Andy R
Background: Few large studies describe initial disease trajectories and subsequent mortality in people with head and neck cancer. This is a necessary first step to identify the need for palliative care and associated services. Aim: To analyse data from the Head and Neck 5000 study to present mortality, place and mode of death within 12 months of diagnosis. Design: Prospective cohort study. Participants: In total, 5402 people with a new diagnosis of head and neck cancer were recruited from 76 cancer centres in the United Kingdom between April 2011 and December 2014. Results: Initially, 161/5402 (3%) and 5241/5402 (97%) of participants were treated with 'non-curative' and 'curative' intent, respectively. Within 12 months, 109/161 (68%) in the 'non-curative' group died compared with 482/5241 (9%) in the 'curative' group. Catastrophic bleed was the terminal event for 10.4% and 9.8% of people in 'non-curative' and 'curative' groups, respectively; terminal airway obstruction was recorded for 7.5% and 6.3% of people in the same corresponding groups. Similar proportions of people in both groups died in a hospice (22.9% 'non-curative'; 23.5% 'curative') and 45.7% of the 'curative' group died in hospital. Conclusion: In addition to those with incurable head and neck cancer, there is a small but significant 'curative' subgroup of people who may have palliative needs shortly following diagnosis. Given the high mortality, risk of acute catastrophic event and frequent hospital death, clarifying the level and timing of palliative care services engagement would help provide assurance as to whether palliative care needs are being met.